Alle origini di L’évolution des formes grammaticales di Antoine Meillet. Linguistica e Scientia un secolo fa (Atti del Sodalizio Glottologico Milanese, 2024)
In 1912 Antoine Meillet published a paper, L’évolution des forms grammaticales, that turned out to be one of the most inspiring contributions in the entire history of linguistics. In the present paper it is suggested that some of the ideas in Meillet’s article were probably stimulated by a letter unpublished so far that was sent to him by Ernesto Rignano, one of the co-editors of Scientia. the journal in which the article was published. The present paper is divided into two parts: in the first, Meillet’s paper will be analysed carefully and the conceptually relevant points will be highlighted, whereas in the second part the text of Rignano’s letter will be briefly commented on, stressing the points that could have stimulated some of Meillet’s reflections on grammaticalization.
Keywords: Grammaticalization; Grammatical Forms; Word Order; Expressive Power